Functional analysis of p53 tumor suppressor in yeast - Smardová, Jana; Smarda, Jan; Koptíková, Jana (Differentiation; research in biological diversity, 2005)
The p53 tumor suppressor protein is a transcription factor that mediates the cell's response to various kinds of stress by preventing cell division and/or inducing apoptosis. p53 gene mutations have been detected in nearly 50% of human cancers. These gene aberrations are mostly missense point mutations located predominantly in the central DNA-binding domain. In addition to the classical inactivating mutations, there are also dominant-negative, gain-of-function, temperature-sensitive, and cold-sensitive, discriminating, superactive p53 mutations, and some mutations that do not inactivate p53 activity. Several approaches have been developed for detection and analyses of p53 mutations: first, immunochemical methods have been developed to detect p53 protein levels; second, molecular analyses targeting changes in DNA structure are utilized; and third, functional assays are used to explore the biological properties of the p53 protein. Functional analysis of separated alleles in yeast targets the transactivation capability of the p53 protein expressed in yeast cells. This method uses p53 mRNA isolated from cells and tissues to produce a p53 product by RT-PCR. This method has undergone continuous improvement and now serves as a powerful tool for distinguishing various functional types of p53 mutations. Understanding the exact impact of p53 mutation on its function is an important prerequisite for establishment of efficient anti-cancer therapies.
Keywords: mutace; Saccharomyces cerevisiae; Tumor Suppressor Protein p53; lidé; geny p53; nádorový supresorový protein p53; Genes, p53; Tissue Distribution; DNA Mutational Analysis; Mutation; tkáňová distribuce; mutační analýza DNA; Humans